Industrial production of limestone calcined clay cement: experience and insights. Issue 1 (25th July 2018) - Krishnan, Sreejith; Emmanuel, Arun C; Shah, Vineet; Parashar, Anuj; Mishra, Geetika; Maity, Soumen; Bishnoi, Shashank
Abstract : The reduction of the clinker factor in cement has emerged as the most promising solution to reduce carbon dioxide (CO2 ) emissions and to improve sustainability. Limestone calcined clay cement (LC 3 ) is a ternary cement where the synergy between calcined clay and limestone allows the reduction of clinker factors to 0·5. In order to understand practical issues in the production of LC 3, such as the selection of raw material and production conditions, industrial production of LC 3 has been carried out at three locations in India. A wide range of raw materials was collected from various parts of India and characterised to evaluate their suitability for the production of LC 3 . Both static and rotary calciners were used for the production of calcined clay. Open- and closed-circuit ball mills were used. Limestones with various impurities and compositions were utilised. It has been observed that lower-grade clay and limestone can be used and that the quality control during the production process can be carried out using widely available techniques. Field trials have shown that the cement can be used without any changes to the existing construction methodologies. This paper discusses the key lessons and insights gained from these trial productions.